The Study of Industrial Water Pollution at Kawasan Perindustrian Jejawi, Perlis - Juliana Ab Rahman (Penerbit Universiti Malaysia Perlis, 2010)
Nowadays, the importance of river quality has become vital and the significance of river quality could not be denied anymore. This study has been conducted to asses the extent of heavy metal and the water quality of the Sungai Jejawi river system. The river was widening for agricultural purposes. Hundred and ten water samples were collected for heavy metal and water quality analysis along Sungai Jejawi. Sampling was conducted four times over a period of a month, six times over a period of weekday and weekends and also 7 times over a period of a week on December 2009. Water quality parameters such as temperature, ph, DO, BOD, COD and ammonical nitrogen were monitored. The results were then compared where possible to the recommended present INWQS and DOE WQI. The physical and chemical water quality analyses were carried out according to the spectrophotometry techniques. The DR2800 Spectrophotometer and X-Ray Fluorescence (XRF) had been used to determine of heavy metals in the samples. Elemental concentrations of Mn, Cu, Zn and Cr were measured. The trend of several pollutants in the river and the statistical analysis of the results were obtained. The result was then compared to the Standard B Environmental Quality (Sewage and Industrial Effluents) Regulations 1979. All the selected heavy metal such as Cu (0.42 mg/L), Mn (0.178 mg/L), Cr (0.091 mg/L) and Zn (0.05 mg/L) had followed the Standard quality. For the XRF determination the trend of heavy metals in water of the Sungai Jejawi system is Ru> Pd >P> Ca> Hf >Al> Cu >Fe >Os. This river was classified into class III, based on Malaysian interim water quality standard criteria (INWQS) which is it can be use as second water supply, but it required conventional treatment. It also can be use as a place for fishing activities. So, it was no doubt if there are fishing activities along Sungai Jejawi, even though it is situates near to the industrial area.